Characteristics of telomere length in patients with hematological diseases (literature review) - Yu. A. Kondratieva; L. P. Mendeleeva (Онкогематология)
Telomeres are protein structures that regulate the process of cellular aging and play the role of a protective “cap” on the end sections of chromosomes. The telomeres of nucleated cells undergo permanent shortening during their lifetime as a result of multiple cycles of DNA replication. The enzyme that provides completion of the missing telomeric repeats at the ends of chromosomes is called “telomerase”. However, recovery of critically short telomeres by telomerase or recombination in somatic cells is limited due to the presence of a large accumulation of unclosed telomeres, which triggers apoptosis. The death of stem cells due to telomere depletion ensures the selection of abnormal cells in which the genome instability contributes to malignant progression. During carcinogenesis, cells acquire mechanisms for maintaining telomeres in order to avoid programmed death. In addition, tumor cells are able to support the telomere's DNA, counteracting its shortening and premature death. Activation of telomere length maintenance mechanisms is a hallmark of most types of cancers. In the modern world, there is an increasing interest in studying the biological characteristics of telomeres. The development of new methods for measuring telomere length has provided numerous studies to understand the relationship between telomere length of human nucleated cells and cancer. Perhaps maintaining telomere length will be an important step, determining the course and prognosis of the disease. The purpose of this review is to provide an analysis of published data of the role and significance of telomere length in patients with hematological malignancies.